CAR‐NK cell in cancer immunotherapy; A promising frontier. Issue 9 (7th July 2021) - Marofi, Faroogh; Abdul‐Rasheed, Omar F.; Rahman, Heshu Sulaiman; Budi, Hendrik Setia; Jalil, Abduladheem Turki; Yumashev, Alexei Valerievich; Hassanzadeh, Ali; Yazdanifar, Mahboubeh; Motavalli, Roza; Chartrand, Max Stanley; Ahmadi, Majid; Cid‐Arreguid, Angel; et al.
Abstract: Chimeric antigen receptors (CARs) have a unique facet of synthetic biology and offer a paradigm shift in personalized medicine as they can use and redirect the patient's immune cells to attack cancer cells. CAR‐natural killer (NK) cells combine the targeted specificity of antigens with the subsequent intracellular signaling ability of the receptors to increase their anti‐cancer functions. Importantly, CAR‐NK cells can be utilized as universal cell‐based therapy without requiring human leukocyte antigen (HLA) matching or earlier contact with tumor‐associated antigens (TAAs). Indeed, CAR‐NK cells can be adapted to recognize various antigens, hold higher proliferation capacity, and in vivo persistence, show improved infiltration into the tumors, and the ability to overcome the resistant tumor microenvironment leading to sustained cytotoxicity against tumors. Accumulating evidence from recent in vivo studies rendering CAR‐NK cell anti‐cancer competencies renewed the attention in the context of cancer immunotherapy, as these redirected effector cells can be used in the development of the "off‐the‐shelf" anti‐cancer immunotherapeutic products. In the current review, we focus on the therapeutic efficacy of CAR‐NK cell therapies for treating various human malignancies, including hematological malignancies and solid tumors, and will discuss the recent findings in this regard, with a special focus on animal studies. Abstract : In the current review, we focus on the therapeutic efficacy of CAR‐NK cell therapies for treating various human malignancies, including hematological malignancies and solid tumors, and will discuss the recent findings in this regard, with a special focus on animal studies.